Formulating a Business Process Outsourcing Strategy to Enhance Competitive Advantage: A Case Study of PT ABC in the Indonesian Outsourcing Industry - Bayu Istantoro; Ahmad Adriansyah; Antyo Pracoyo; Batara Maju Simatupang (Publikasi Indonesia, 2025)
The Indonesian outsourcing industry is currently dominated by low-margin Manpower Outsourcing (MPO) services, with limited development in high value-added segments such as Business Process Outsourcing (BPO). Most domestic providers face stagnant profit margins below 3%, intense price competition, and heavy reliance on labor-intensive operations. Against this backdrop, digital transformation and BPO service automation have become critical differentiators in global markets, yet remain underutilized in Indonesia. This study aims to formulate a Business Process Outsourcing (BPO) development strategy at PT ABC to enhance its competitive advantage within Indonesia’s outsourcing industry. The research adopts a qualitative single-case study approach, leveraging internal documentation, strategic meeting transcripts, and informal interviews with management. Using the Playing to Win framework, supported by the VRIO and McKinsey 7S models, this study explores how PT ABC can shift from Manpower Outsourcing dominance to a more balanced portfolio emphasizing BPO services. Results indicate that although BPO currently contributes only 11.2% of gross profit, it holds a growing profit margin—rising from 27.9% (2022) to 32.4% (2023)—and potential for expansion in the BFSI sector. Strategic implications include client diversification beyond PT XYZ, technological innovation, and enhanced workforce capabilities. The study finds that implementing data-driven systems and thematic training programs is essential to support sustainable transformation. These insights offer a practical roadmap for PT ABC to increase profitability and reduce dependency on labor-intensive services.